1997
DOI: 10.1006/dbio.1997.8738
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Receptor Tyrosine Kinase Kit Is Required for the Proliferation of Melanoblasts in the Mouse Embryo

Abstract: The development of neural crest-derived melanocytes, as well as haematopoietic and germ cells, is affected by mutations of the Kit and Mgf genes, which lead to dominant spotting (W) or steel (Sl) phenotypes. Mgf codes for the ligand of the receptor tyrosine kinase encoded by the Kit locus. KitW-v, a point mutation exerting a dominant negative effect, causes a substantial reduction in tyrosine kinase activity of the Kit receptor and leads to a characteristic pigmentation phenotype, namely dilute coat colour and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
327
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(343 citation statements)
references
References 32 publications
14
327
0
2
Order By: Relevance
“…Although many tumor cells were negative for RPE65, the marker of terminally differentiated RPE cells, some cells, especially in the pigmented areas of the tumors, expressed Pmel17, a marker of premelanosomes (Supplementary Figure S6). Furthermore, X-gal staining of eye sections from Tyrp1::NotchIC/1; Dct::LacZ/1 mice (Mackenzie et al, 1997) confirmed that the cells forming the pigmented mass in eyes were from RPE origin (Figure 3d). …”
Section: Activated Notch Signaling Maintains Rpe Cells In a Proliferamentioning
confidence: 75%
“…Although many tumor cells were negative for RPE65, the marker of terminally differentiated RPE cells, some cells, especially in the pigmented areas of the tumors, expressed Pmel17, a marker of premelanosomes (Supplementary Figure S6). Furthermore, X-gal staining of eye sections from Tyrp1::NotchIC/1; Dct::LacZ/1 mice (Mackenzie et al, 1997) confirmed that the cells forming the pigmented mass in eyes were from RPE origin (Figure 3d). …”
Section: Activated Notch Signaling Maintains Rpe Cells In a Proliferamentioning
confidence: 75%
“…We maintained Kit w-v and Pax3 Splotch mice on a C57 background and Ednrb s-l mice on a SSL/Le background. We crossed mice carrying the Dct-lacZ reporter transgene (provided by M. Shin (Fox Chase Cancer Center, Philadelphia, Pennsylvania, USA) with the permission of I. Jackson (MRC Human Genetics Unit, Western General Hospital, Edinburgh, Scotland)) 24 for at least three generations to C3HeB/FeJ mice. All experiments were carried out under a protocol approved by the Stanford Administrative Panel on Laboratory Animal Care.…”
Section: Methodsmentioning
confidence: 99%
“…Many white-spotting mutations are thought to act by compromising the proliferation or survival of melanoblasts, such that progenitor pools are exhausted before migration is complete [23][24][25][26] . If this is the case, the increased number of early melanoblasts caused by Dsk1 and Dsk7 mutations might rescue white spotting, regardless of the underlying cause.…”
Section: Signaling Pathway Interactionsmentioning
confidence: 99%
“…The geographic separation between follicular melanocyte stem cells (bulge region) relative to their differentiated progeny (hair bulb) permitted relatively simple quantitative analysis of each population. Using transgenic mice in which the melanocyte lineage was tagged by LacZ (Mackenzie et al 1997), it was observed that senile graying is associated with progressive depletion of the stem cell pool (Nishimura et al 2005). Melanocyte stem cell depletion was preceded by the stochastic appearance of pigmented melanocytes within the bulge region-a population that was not maintained, suggesting that it may represent a dead-end route away from the stem cell pool.…”
Section: Pigmentationmentioning
confidence: 99%